2001
DOI: 10.1191/095968301680223486
|View full text |Cite
|
Sign up to set email alerts
|

July mean temperature and annual precipitation trends during the Holocene in the Fennoscandian tree-line area: pollen-based climate reconstructions

Abstract: July mean temperature and annual precipipation during the last 9900 cal. yr BP were reconstructed from pollen assemblages preserved in a sediment core from northern Finland. Quantitative reconstructions were performed using a modern pollen-climate calibration model based on weighted-averaging partial least squares regression. The predictive ability of the model was evaluated against modern meteorological data using leave-one-out cross-validation. The prediction error for July mean temperature is c. 1.0°C and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
302
1
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 347 publications
(337 citation statements)
references
References 49 publications
31
302
1
3
Order By: Relevance
“…The temperature estimates based on macrofossils (for example, tree-line position) indicate a rapid and stable warming after 10,000 cal year BP across the entire northern Scandinavia (Seppä and Birks 2001). Climate reconstructions for central Sweden using pollen spectra from Lake Gilltjärnen sediments show a rapid increase in summer temperatures from 10.0 to 12.0°C between 10,700 and 9000 cal year BP.…”
Section: Early Holocene Oscillationsmentioning
confidence: 99%
See 3 more Smart Citations
“…The temperature estimates based on macrofossils (for example, tree-line position) indicate a rapid and stable warming after 10,000 cal year BP across the entire northern Scandinavia (Seppä and Birks 2001). Climate reconstructions for central Sweden using pollen spectra from Lake Gilltjärnen sediments show a rapid increase in summer temperatures from 10.0 to 12.0°C between 10,700 and 9000 cal year BP.…”
Section: Early Holocene Oscillationsmentioning
confidence: 99%
“…In central and southern Norway, the snow line (equilibrium line altitude) lowered by 200 m (Nesje and Dahl 2001;Nesje 2009). The altitude of the upper boundary of arboreal vegetation also lowered (Seppä and Birks 2001;Seppä et al 2007Seppä et al , 2008.…”
Section: The '82 Ka Cold Event'mentioning
confidence: 99%
See 2 more Smart Citations
“…In a seminal paper, Bond et al [2] reported variations of ice-rafted sand and sediment in the northeastern North Atlantic that imply 1500yr cycles in the strengths of the Drift, the SAC flow, and NADW formation with corresponding climatic effects. However, the reality of the 1500yr higher latitude climate cycle has not been well confirmed in the Fennoscandian climate proxy record of Seppä and Birks [3], possibly due to overprinting of the proxies by random regional variations. The cause of a related climatic anomaly, the Little Ice Age, has also been vigorously debated.…”
Section: Introductionmentioning
confidence: 99%